Hydrogenolysis of 5-Hydroxymethylfurfural to 2,5-Dimethylfuran Over a Modified CoAl-Hydrotalcite Catalyst - Xia, Jing; Gao, De; Han, Feng; Lv, Ruifu; Waterhouse, Geoffrey I. N.; Li, Yan (Frontiers in Chemistry, 2022)
The catalytic hydrogenolysis of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) is a promising route towards sustainable liquid fuels with a high energy density. Herein, a novel CuCoNiAl-containing mixed metal oxide catalyst (CuCoNiAl-MMO) was prepared by calcination a layered double hydroxide (LDH) precursor in N2 at 500 °C, then applied for the catalytic hydrogenolysis of HMF to DMF. The effects of reaction time, reaction temperature and hydrogen pressure on DMF selectivity were investigated. Under relatively mild reaction conditions (180 °C, 1.0 MPa H2, 6.0 h), CuCoNiAl-MMO showed both a high initial activity and selectivity for hydrogenolysis of HMF to DMF, with HMF conversion rate of 99.8% and DMF selectivity of 95.3%. Catalysts characterization studies using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) revealed the presence of various metal oxides and metallic copper on the surface of the CuCoNiAl-MMO catalyst, with the presence of mixed metal-oxide-supported metallic Cu nanoparticles being responsible good hydrogenolysis activity of the catalyst for selective DMF synthesis.